Road safety of school children : assessing the walkability of selected public elementary school (PES) neighborhoods in Quezon City using walkability index and localized virtual-STEPS. - Cruz, Giel Sabrine P. (School of Urban and Regional Planning, University of the Philippines Diliman, 2022)
The main objective of the study is to assess the built environment (BE) walkability of three public elementary school (PES) neighborhoods in Quezon City using macro-scale and macro-scale assessment tools, namely walkability index and localized Virtual-STEPS-an auditing tool specifically designed to assess built environment remotely. In doing so, the study utilized Google Street View, a web service that provides panoramic views of streets that have been widely used in virtual auditing methods around the world. With children at high risk of road traffic injury, BE condition has become a crucial and essential factor in promoting walking as a safe, viable, and sustainable transport mode around PES neighborhoods. Results show that Bagong Pag-asa PES neighbourhood scores the highest in both macro-and micro-scale assessments, and scores the lowest in perceived risk. Among the three, Bago Bantay PES neighbourhood has the highest perceived risk rating, which generally arises from poor pedestrian infrastructure, lack of assistance from barangay traffic aids, and lack of road signs to manage the motorized traffic. Perceived risk has a high to very high negative correlation with localized Virtual-STEPS and walkability index, and has a negative and significant statistical association with pedestrian infrastructure (95% CI:-7.61,-2.57,p=0.025). Recommended policies and strategies include having an effective advocacy campaign aiming to build the capacity and skills of children on safe practices when walking to and from schools, strengthening the data collection system of both national and local government agencies, improving pedestrian infrastructure to cater to all pedestrians of various ages an degrees of mobility, developing policies against sidewalk obstruction and disorder, and regulating the presence of motorized traffic in strategic areas.